Good scientific practice: A behavior-analytical discussion - Guazi, Taísa Scarpin [UNESP]; Laurenti, Carolina; Carrara, Kester [UNESP] (My University, 2018)
The publication of a report with guidelines of good scientific practice by CNPq in 2011 is considered one of the milestones in the discussion on integrity in science in Brazil. The objective of this work was to discuss such guidelines under a behavioral approach, considering them as rules. Although rules offer advantages to the acquisition of good practices by researchers, the teaching of morality should not be restricted to the exposure of these professionals to these guidelines, but provide conditions for them to be sensitive to the different ethical issues that may arise in the context of the production of scientific knowledge. The analysis of the document published by CNPq also shows that the consequences of misconduct and good practices in science are postponed and nonspecific. On the other hand, the consulted literature correlates scientific fraud with the demands of scientific productivity: in some cases, the misconduct seems to allow the researcher to adapt to the demands of productivity. Moreover, consequences associated with academic productivity contingencies are more immediate and may, therefore, exert more control over the behavior of the scientist. The discussion about scientific fraud, in this sense, implies considering the current academic contingencies.
Boas práticas científicas: Uma discussão analítico-comportamental
Keywords: Behavioral analysis; Fraud; Guideline adherence; Science; Scientific misconduct; Technology legislation